PENYEBAB COST OVERRUN PADA PROYEK KONSTRUKSI - Cut Mutiawati (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2012)
Abstract: Cost control is one of the important thing in construction project. If the cost of construction is uncontrollable, it will cause cost overrun. Cost overrun can be caused by many factors such as material, man power and heavy equipment cost. This research want to investigate the dominant factor that cause cost overrun. Data was collected by questionaires that consists of 66 Variables. The variables were divided in 3 phases, 33 variables in planning phase, 23 variables in implementation phase and 2 variables in maintenance phase. Assesment of dominant level on this research were carried out in 5 measurement scale: 1 (very not dominan), 2 (less dominant), 3 (rarely dominant), 4 (dominant) and 5 (very dominant). The questionaires were distributed to contractor grade 5, 6 and 7 that execute the construction project in Aceh. Data analysis were done by calculating the average value (mean). The results shown that there are 51 variables cause of cost overrun with “dominant” category consisting of 13 variables at planning phase, 37 variables at implementation phase and 1 variable at maintenance phase with mean of 3,75 ≥ x ≥ 2,5. While 15 variables is categoried as